Poincaré Beams at the Tight Focus: Inseparability, Radial Spin Hall Effect, and Reverse Energy Flow - Victor V. Kotlyar; Sergey S. Stafeev; Vladislav D. Zaitsev; Alexey M. Telegin (Photonics, 2022)
The family of Poincaré beams has three parameters, including two real-valued angular parameters, which specify a definite polarization state on the Poincaré sphere, and a third integer parameter n specifying the beam singularity order. We show theoretically and through a numerical simulation that, while being inseparable and not allowing for the separation of polarization and orbital degrees of freedom in the general case, the Poincaré beams display remarkable properties when tightly focused. We find that at n = 2, a reverse energy flow occurs near the optical axis, which is mathematically expressed as the negative projection of the Poynting vector. We also reveal that given certain parameters of the Poincaré beams, the energy flow rotates around the optical axis due to spin–orbital conversion. We also reveal a radial optical Hall effect that occurs at the tight focus of Poincaré beams, when the on-axis components of the spin angular momentum vector have different signs on certain different-radius circles centered at the focal spot center.